Students' satisfaction with simulated clinical experiences: validation of an assessment scale - Batista, Rui Carlos Negrão (2014)
Objective: validate an assessment instrument of nursing students' satisfaction with simulated clinical experiences. Method: a 17-item scale was applied to students from the Teaching Diploma Program in Nursing, after a set of simulated clinical experiences. Factorial analysis with orthogonal varimax rotation was used, and the internal consistency was estimated to determine the validity of the scale. Results: in a sample of 181 students, we found a high correlation between practically all items and the total scale, with an Alpha coefficient of 0.914. The scale items were divided in three factors: practical dimension, realism dimension and cognitive dimension, with good internal consistency coefficients of 0.89; 0.88 and 0.73, respectively. Conclusion: the scale complies with the validity requisites, revealing a high potential for use in research.